THE MOSQUE MANAGEMENT INNOVATION: EXPLAINING PROCESS AND DRIVING FORCES - Ihsan Rahmat; Ashadi Cahyadi; Indra Pratama Putra Salmon (UIN Sunan Kalijaga, 2019)
This study aims to explain the innovation process and driving factors in the mosque. This is important because innovation is too focused on the economic sector, forgetting religious institutions. Modern mosques continue to display stretching innovation, but previous studies have not been explaining how to the process. 12 innovative programs in Masjid At-Taqwa Anggut owned by Bengkulu City Government have been appointed as cases. We conducted in-depth interviews with 11 mosque officials and 7 days were used for observation. Seeing how the innovation process, we have used keyword discovery techniques and data categorization. We found a relatively similar pattern in every program. The innovation process in At-Taqwa Anggut starts the needs of worshipers, idea generation, Islamic focus discussion, development, and program execution. Requesting perspective to the Mosque Sharia Council (Islamic expert) is an interesting process. It turned out to be a unique finding because the general framework had not yet been published. Three of the driving factors considered to have a strong influence are the mayor's leadership, the love of the mosque, and the spirituality motivation in the motto of fastabikul khairat.Keywords: Innovation, Mosque Management, Religious Institution